65-3x=42x+15

Simple and best practice solution for 65-3x=42x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 65-3x=42x+15 equation:


Simplifying
65 + -3x = 42x + 15

Reorder the terms:
65 + -3x = 15 + 42x

Solving
65 + -3x = 15 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
65 + -3x + -42x = 15 + 42x + -42x

Combine like terms: -3x + -42x = -45x
65 + -45x = 15 + 42x + -42x

Combine like terms: 42x + -42x = 0
65 + -45x = 15 + 0
65 + -45x = 15

Add '-65' to each side of the equation.
65 + -65 + -45x = 15 + -65

Combine like terms: 65 + -65 = 0
0 + -45x = 15 + -65
-45x = 15 + -65

Combine like terms: 15 + -65 = -50
-45x = -50

Divide each side by '-45'.
x = 1.111111111

Simplifying
x = 1.111111111

See similar equations:

| 18x^2-59x+33=0 | | 3x-6=3(2x-5) | | 8y-12= | | f(x)=0.25+x^3 | | 5t+4=3t+11 | | 0=-.4x^2+40x-360 | | -4x=32-7(x+2) | | 30=4 | | y^2-6y-x=0 | | 50=-4.9x^2+40x+89 | | 20x-28y=0 | | y=-4.9x^2+40x+89 | | x+11=7x-7 | | Z^2+(1+i)z+i=0 | | -8x^2+13x+50=0 | | 5x-(4x+7)=4x-28 | | 17-6y-8+10y= | | 4x+2y=172 | | 5(e+7)=2e | | x+x^2+x^3=3000000 | | 314x+132x=35000 | | 8-14x=17-17x | | 36y^2-25x^2=900 | | 6y-8=2y+7 | | -4=0,5x | | 36x^2-25y^2=900 | | (2xy+4x+3)dx+(x^2+2y-5)dy=0 | | 6x-3x+3=4x-33 | | 2x(3x-1)=9 | | 6m+10=52 | | 5x-5y=2y+8 | | 20x+40y=1500 |

Equations solver categories